Switzerland Committed to Innovation. The Swiss Network of Technology Assessment (Italian Journal of Public Health, 2005)
Switzerland showed its commitment to innovation in health care since the early 80th, implementing agenciesand government units with the mission to promote and to appropriately govern innovation. The SwissNetwork of Technology Assessment (SNHTA) was founded in 1998. The aim is the promotion andimplementation of Health Technology Assessment projects in Switzerland by providing a neutral forum forthe identification and the pursuit of common interests. This includes the coordination, exchange anddissemination of experiences of HTA projects and the implementation of the results. The collaboration ininternational projects is a priority. Ultimately SNHTA has the goal to improve efficacy, cost effectiveness andsocial accountability. An inventory survey amongst the members confirmed a high level of diversespecialised competencies, mainly employed within the institution. Only 20% of the HTA specificcompetencies are used for external activities. The need for integration of all partners in the field ofinnovation in a network has been recognised by the Swiss government. This lead to the creation of awebplatform in which all players involved in the business of medical technologies are involved. This platform(swiss medtech), includes patients, insurers, industry, universities and professional organisations. Thejoined activities include agreements on intellectual property and the integrated patient care chain.New ways to connect players in innovation are needed to face the challenge of increasing costs anddiminishing resources.
Keywords: HTA; innovation; Switzerland; network